Advances of berberine against metabolic syndrome-associated kidney disease: Regarding effect and mechanism - Ya-Fei Liu; Huan-Huan Wang; Yin-Hong Geng; Liang Han; Sheng-Hao Tu; Hui Wang (Frontiers in Pharmacology, 2023)
The prevalence of metabolic syndrome (MetS) is drastically growing worldwide, resulting in MetS-associated kidney disease. According to traditional theories, preventing blood pressure, lipid, glycose, and obesity and improving insulin resistance (IR), a couple of medications are required for MetS. It not only lowers patients’ compliance but also elevates adverse reactions. Accordingly, we attempted to seek answers from complementary and alternative medicine. Ultimately, berberine (BBR) was chosen due to its efficacy and safety on MetS through multi-pathways and multi-targets. The effects and mechanisms of BBR on obesity, IR, diabetic nephropathy, hypertension, hyperlipidemia, and hyperuricemia were elaborated. In addition, the overall properties of BBR and interventions for various kidney diseases were also collected. However, more clinical trials are expected to further identify the beneficial effects of BBR.